Effects of light intensity on growth and nutritive value of Brachiaria humidicola - Omar, Syahirah (2017)
Koronivia grass is a common name for Brachiaria humidicola sp. and it is a leafy, procumbent, creeping, stoloniferous perennial tropical grass. Brachiaria humidicola is tolerant of poor drainage and can withstand short term flooding in valley bottoms. It has been shown that decreasing light intensities may affect the arrangements of plant leaf tissues such as mesophyll cell volume (Chabot and Chabot 1977), amount of vascular and support tissues, and cuticle thickness (Wilkinson and Beard 1975). General objective for this research was to investigate the nutritive value and growth response of Brachiaria humidicola (koronivia grass) towards light intensity. The research hypothesis was light intensity have significant effects on the growth and nutritive value of Brachiaria humidicola, while the specific objectives were to determine the dry matter production per hectare of koronivia grass towards different light intensity, to determine the nutritive value of koronivia grass towards different light intensity and to determine the botanical composition and leaf-stem ratio of koronivia grass towards different light intensity. The response of koronivia grass to sunlight intensity were assessed in two month of experiment from early August until September 2016 at the Field 15, Universiti Putra Malaysia using randomized complete block design (RCBD). The treatment was the intensity of light (100% (full sunlight), (50% sunlight (partial shade)) and (30% sunlight (70% shade)) that were manipulated by black shading net imposed on wood frame with 5 feet height x 3m wide and was arranged in the 2 x 3 plotting system. The production, morphological aspects and nutritive value were assessed in this project. The grass was sampled and cut 3 inches height above the ground level at 18 days for each cycle. There were significant different (P<0.05) on ADF%, CP%, and dry matter yield among treatments towards different light intensity. The dry matter production decrease as the light intensity decreased. The dry matter production decreased from 37.63 tan/ha at 100 % light intensity, 27.20 tan/ha and 25.86 tan/ha at 50 % and 30 % light intensity. However, crude protein % increased as light intensity decreased among the treatments. The crude protein % increased from 6.6 % at 100 % light intensity to 8.5 % and 9.8 % at 50 % and 30 % light intensity respectively. There were no significant different on Neutral Detergent Fiber (NDF %) and leaf to stem ratio. There was no significant different among treatment in leaf to stem ratio and ADF %. The leaf to stem ratio was higher at 100 % light intensity and the ADL % was higher at 30 % light intensity. It is concluded that the grass that was grown under 30 % and 50 % light intensity gave the best result with the total production of dry matter similar to the control and had high protein content. However, the increase in N-content of shaded plants may improve the feeding value of herbage.